Neuromuscular adaptations in running - Braun, W. A. (Routledge handbook of ergonomics in sport and exercise, 2016)
Run training, as with all forms of physical exercise training, stimulates the development of adaptations that should benefit the performance of the task. In the case of distance running, these adaptations often result in improved economy of transport (i.e. lower energy cost to maintain a fixed running speed). Mechanisms behind training-related improvements in running economy fall primarily into two broad categories: metabolic adaptation and neuromuscular adaptation. The focus of this chapter will be on factors that may contribute to neuromuscular adaptations and improvements in running economy primarily in distance runners. In conjunction with this, common training practices will be explored, including: (1) incorporation of resistance training as a means of supporting the performance of running; (2) adaptations that result from chiefly `run-only` training; and (3) possible influences of barefoot running versus shod running on neuromuscular adaptations that develop from running. The chapter begins with a general exploration of the relationship between endurance run training and neuromuscular factors.